KAJIAN SIFAT FISIK FILM TIPIS NATA DE SOYA SEBAGAI MEMBRAN ULTRAFILTRASI - Puspawiningtiyas, Endar; Damajanti, Neni (Techno Jurnal Ilmu Teknik, 2011)
âWheyâ is one of liquid waste water that was produced from tofu making process. There are many research that processÂ  whey to waste water that ready to dispose. One of whey utilization to product that more useful is as of nata making raw material, that often called nata de soya. The contain of nata is cellulose (Bergenia,1982). Cellulose that produced via fermentation process by bacteria often called microbial cellulose. Based of physic and chemical properties that owned by microbial cellulose, be requiredÂ  a study about possibility nata de soya as separated membrane especiallyÂ  ultrafiltration membrane.The Goal of this research are to studyÂ  about influence of NaOH and H2SO4 concentration to density,Â  swelling degree, water flux, nata de soya membrane rejection.The result of this research show that NaOH and H2SO4 treatment influence to phisical and chemical properties of nata de soya thin layer. Greatest density and smallest swelling degree are 0,94gr/cm3 and 210% at NaOH 6 % treatment. Greatest density and smallest swelling degree are 0,92gr/cm3 and 216% at H2SO4 8 % treatment. Flux value generated atÂ  several NaOH concentration average 18,89 Lm-2jam-1bar-1.Â  By Murder (1996), ultrafiltration membrane has operational presure range 1.0 â 5.0 bar and water flux 10 -50 Lm-2jam-1bar-1, thus flux test result show that nata de soya thin layer adequate as ultrafiltration membrane. Smallest water flux value is obtained at NaOH 6 % concentration is 15.68Â  Lm-2jam-1bar-1. Fluctuating graph at influence of NaOH concentration to rejection coefficient has not been able to conclude best treatment to obtain maximum rejection coefficient, but overall average rejection coefficient at NaOH treatment to nata de soya thin layer is 47,6%.Â Keyword : ultrafiltration membrane, nata de soya